Casa de Meche, the importance of selecting the correct beneficiary in an alternative post-disaster construction process - Villacís T., Enrique (2018)
More than a year ago, Ecuador suffered a 7.8 Mw earthquake that was devastating, the automatic response was to run to the affected areas and rebuild.  Meche’s House is an alternative: the crisis as an opportunity to experiment and consolidate popular construction systems based on an endogenous and holistic approach. This study evaluates two case studies and their contrasting methodologies in their process of selecting beneficiaries for post-disaster reconstruction: Casa Lista of Mutualista Pichincha and La Casa de Meche, differentiating both cases from analyzing their different approaches: the automatic one, non-reflective and product-based, the other analytical and process-based. Founded on experience and how different processes need different beneficiaries, this study will raise some questions about the effectiveness, pros, cons, and perspectives of different approaches to rightly choose the beneficiary for the reconstruction process after a natural disaster. Each process focuses on a specific beneficiary; it is not possible to generalize. The processes that result in trained and resilient people as in Meche’s House are those that have had the best results.